Reactive power regulation strategy for WTGs based on active disturbance rejection control - Xue, Shuilian; Yin, Zhilong; Wang, Zhiguo; Yu, Feng; Chen, Hailiang (Frontiers in Energy Research, 2024)
With the large-scale interconnection of wind power generation, the voltage problem of power system becomes more and more prominent. Compared with adding external reactive power compensation devices, it is more economical and responsive for fans to adjust their control strategies to provide reactive power support. To make full use of reactive power supported by wind turbines, the mathematical model of DFIG wind turbines is constructed to characterize the reactive power boundary of wind turbines. Then, active disturbance rejection control (ADRC) is used to generate voltage control signal to effectively improve the unit's reactive response speed, in addition, variable gain coefficient is used to adjust the reactive power output of the unit, which effectively improves the reactive power response speed and its control adaptability and robustness under the change of power grid conditions. Finally, the simulation model of WTG is built based on Matlab/Simulink simulation software, and different fault locations are perturbed, and the effectiveness of reactive power support of the proposed ADRC-based strategy is simulated and verified.